2019
DOI: 10.3390/min9090525
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of Possible Leaching Control Mechanisms for Chromium and Vanadium in Electric Arc Furnace (EAF) Slags Using Combined Experimental and Modeling Approaches

Abstract: In this study, possible leaching control mechanisms for Cr and V in electric arc furnace slags were investigated by using a multi-methodological approach. Aside from chemical and mineralogical bulk analyses, special emphasis was given to surface investigations of the slags prior to and after leaching. In addition, pH dependence leaching tests were performed and the obtained data were evaluated with hydrogeochemical models. Investigations revealed that Cr and V are mainly bound in spinel and wuestite as well as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 23 publications
0
23
0
Order By: Relevance
“…For the laboratory experiments, a collective EAF slag sample (sample A) from a previous study [9] was used, which showed high FeO and low SiO 2 abundances and increased V and Cr leaching compared to the other samples investigated. The sampling was performed in 2016 and was assigned to the production of one steel charge during standard operating conditions.…”
Section: Sample Selectionmentioning
confidence: 99%
See 4 more Smart Citations
“…For the laboratory experiments, a collective EAF slag sample (sample A) from a previous study [9] was used, which showed high FeO and low SiO 2 abundances and increased V and Cr leaching compared to the other samples investigated. The sampling was performed in 2016 and was assigned to the production of one steel charge during standard operating conditions.…”
Section: Sample Selectionmentioning
confidence: 99%
“…For comparison, this study also presented one EAF slag sample (sample C) from a second steel plant, which leached significantly lower amounts of V and Cr than sample A and was characterized by a FeO/SiO 2 ratio of approximately one [9].…”
Section: Sample Selectionmentioning
confidence: 99%
See 3 more Smart Citations